Reaktualisasi Makna Makar dalam AlQur’an Menurut Wahbah Az-Zuhaili di Era Modernitas - Khairani, Aufa (Asian Journal of Islamic Studies and Da'wah, 2023)
Destroy the truth. Trick This power can be done by spreading rumors, slander, etc by causing chaos. There are also those who interpret it as turning others away from what they want by deception bad sense. In this thesis the author will discuss treason that occurred in the era of modernity and what crimes are occurring now, the method used by the library, the type of research is qualitative. And in this research, the method used by researchers is method Tahlili Tafsir Tahlili (Analytical). In today's era, there are many crimes that have emerged, including theft, online fraud, online loans, sending links, online investigations, buying and selling fraud, and fake application websites.